2008
DOI: 10.1051/forest:2008003
|View full text |Cite
|
Sign up to set email alerts
|

Response of Scots pine (Pinus sylvestris L.) and pubescent oak (Quercus pubescens Willd.) to soil and atmospheric water deficits under Mediterranean mountain climate

Abstract: . Response of Scots pine (Pinus sylvestris L.) and pubescent oak (Quercus pubescens Willd.) to soil and atmospheric water deficits under Mediterranean mountain climate. Annals of Forest Science, Springer Verlag/EDP Sciences, 2008, 65 (3), pp.1. Ann. For. Sci. 65 (2008) Abstract -The physiological responses to water deficits of Scots pine (Pinus sylvestris L.) and pubescent oak (Quercus pubescens Willd.) were studied under Mediterranean mountain climate. Minimum leaf water potentials were −3.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
72
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 41 publications
13
72
1
Order By: Relevance
“…They compared their results with estimates from the literature due to the difficulty in validating these kinds of regions using sap flow measurements. Nagler et al (2005Nagler et al ( , 2007 (Poyatos et al, 2008). However, in the case of MODIS ET d modelling, the validation shows a higher RMSE, which suggests that higher spatial resolution is needed for heterogeneous areas.…”
Section: Figmentioning
confidence: 82%
See 1 more Smart Citation
“…They compared their results with estimates from the literature due to the difficulty in validating these kinds of regions using sap flow measurements. Nagler et al (2005Nagler et al ( , 2007 (Poyatos et al, 2008). However, in the case of MODIS ET d modelling, the validation shows a higher RMSE, which suggests that higher spatial resolution is needed for heterogeneous areas.…”
Section: Figmentioning
confidence: 82%
“…Instantaneous values (15-min averages) were then summed to compute daily stand transpiration. Further details on the methodology and results of sap flow measurements used in this study can be found in Poyatos et al (2005Poyatos et al ( , 2008.…”
Section: Sap Flow Measurements and Upscaling To Stand Transpirationmentioning
confidence: 99%
“…The difference between Ψ pd and Ψ md (|Ψ md -Ψ pd |) increased with decreasing Ψ pd , therefore allowing a greater increase in the driving force for transpiration as edaphic drought developed (Poyatos et al, 2008). A decrease of seedling water potential affected negatively to stomatal conductance and net assimilation rate during summer drought, irrespective of age class.…”
Section: Discussionmentioning
confidence: 99%
“…The response of downy oak to climate warming was different from Scots pine and produced an increased probability of occurrence throughout the study region. Previous research has demonstrated that downy oak is better adapted than Scots pine to both short-and long-term drought, due to its different physiological responses, i.e., stomata closure, resistance to embolism, and seedling vitality (Eilmann et al 2006;Poyatos et al 2008;Morán-López et al 2012).…”
Section: Discussionmentioning
confidence: 99%